The Influence of HR Development Strategies on the Performance of KJKS BMT Managers for Bina Ummat Sejahtera KCU Grobogan: Pengaruh Strategi Pengembangan SDM terhadap Kinerja Pengelola KJKS BMT Bina Ummat Sejahtera KCU Grobogan - Dede Mariana; Novi Vizainiyah; Suwanto Suwanto (Academia Open, 2019)
HR development is part of the company's internal management. As a part that has a big influence on the company, this certainly cannot be taken lightly. This study aims to explain the effect of education on the performance of the managers / employees of KJKS BMT Bina Ummat Sejahtera, the effect of training on the performance of KJKS BMT Bina Ummat Sejahtera managers / employees and the effect of education and training together on the performance of KJKS BMT Bina Ummat Sejahtera managers / employees. Quantitative descriptive research methods are applied to explain this relationship. From the hypothesis test using the F test, it is known that simultaneously the Education (X1), Training (X2) variables have a significant effect on Job Performance (Y). The coefficient of determination (R2) is 0.784, which means the variable education (X1), training (X2) can explain the variable effect of work performance (Y) of 78.4% while the remaining 21.6% is explained by other variables not included in this research model, for example (factors age, health, etc.). It is hoped that KJKS BMT Bina Ummat Sejahtera KCU Grobogan will be able to develop education and training on an ongoing basis in order to improve the quality of human resources so that their abilities will increase in order to increase work productivity along with target achievement and work performance.